2018
DOI: 10.1021/acsomega.8b01290
|View full text |Cite
|
Sign up to set email alerts
|

Dirhenium Coordination Complex Endowed with an Intrinsically Chiral Helical-Shaped Diphosphine Oxide

Abstract: A one-pot, multicomponent strategy was used to synthesize the first example of the dirhenium carbonyl coordination complex 2 , in which the two metal atoms are connected through a chiral helical-shaped diphosphine oxide. Thanks to the flexibility of the helix of helicene 1 , complex 2 was isolated in quite a good yield as a stable compound. It was characterized by analytical and spectroscopic techniques as well as by single-crystal X-ray anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The design and synthesis of metallocycles such as cages, helicates, and simple-to-complex topological architectures via coordination-driven self-assembly have been gaining significant attention owing to their potential applications in materials and medicinal fields. Further, new aesthetically appealing molecular architectures including intricate topological metallocyclic architectures such as metallo-links (a series of interlocked metallocyclic rings where at least one ring has to be broken to separate them) and metallo-knots similar to those found in nature can be prepared using the self-assembly. Among various topologies, “figure-eight” architecture is one of the elegant self-assembled structures, which is found in natural systems such as Lissoclinamide 7, the recombinant structure of circular DNA and marine alkaloid. , However, very few examples of “figure-eight”-shaped metallocycles are known until now. The design and synthesis of “figure-eight”-shaped metallocycles and other metallocyclic architectures using various metal precursors and organic building units are important in the development of the field, which might yield molecules having various potential applications in the near future. Among the few metal ion-based coordination-driven approaches, the fac -[Re(CO) 3 ] core-based self-assembly method is one of the methods to construct neutral homoleptic and heteroleptic metallocycles, which have potential applications in the field of host–guest encapsulation, catalysis, selective reactivity, sensing, and as bioactive agents. Although a considerable number of synthetic principles for the preparation of various sizes and shapes of fac -[Re(CO) 3 ] core-based metallocycles are currently available, synthetic approaches for preparing “figure-eight” topology, complex-knot, and complex-link-shaped metallocycles are scarce. In addition to the metal core, the nature of the ligand is crucial to obtaining com...…”
Section: Introductionmentioning
confidence: 99%
“…The design and synthesis of metallocycles such as cages, helicates, and simple-to-complex topological architectures via coordination-driven self-assembly have been gaining significant attention owing to their potential applications in materials and medicinal fields. Further, new aesthetically appealing molecular architectures including intricate topological metallocyclic architectures such as metallo-links (a series of interlocked metallocyclic rings where at least one ring has to be broken to separate them) and metallo-knots similar to those found in nature can be prepared using the self-assembly. Among various topologies, “figure-eight” architecture is one of the elegant self-assembled structures, which is found in natural systems such as Lissoclinamide 7, the recombinant structure of circular DNA and marine alkaloid. , However, very few examples of “figure-eight”-shaped metallocycles are known until now. The design and synthesis of “figure-eight”-shaped metallocycles and other metallocyclic architectures using various metal precursors and organic building units are important in the development of the field, which might yield molecules having various potential applications in the near future. Among the few metal ion-based coordination-driven approaches, the fac -[Re(CO) 3 ] core-based self-assembly method is one of the methods to construct neutral homoleptic and heteroleptic metallocycles, which have potential applications in the field of host–guest encapsulation, catalysis, selective reactivity, sensing, and as bioactive agents. Although a considerable number of synthetic principles for the preparation of various sizes and shapes of fac -[Re(CO) 3 ] core-based metallocycles are currently available, synthetic approaches for preparing “figure-eight” topology, complex-knot, and complex-link-shaped metallocycles are scarce. In addition to the metal core, the nature of the ligand is crucial to obtaining com...…”
Section: Introductionmentioning
confidence: 99%
“…Lately, the study of organometallic complexes has departed from solely fighting cancer and has been proposed as new solutions to the problems posed by bacterial resistance to antibiotic treatments [4]. Largely studied, owing to their photophysical and photochemical properties, and valuable in many applications such as bioimaging [5,6], luminescence [7,8], radiolabeling [9] and in catalysis [10][11][12][13], several studies have now revealed the high potential of rhenium tricarbonyl complexes (fac-[Re I (CO) 3 ] + ) as antimicrobial [14][15][16][17][18][19][20][21][22], anticancer [23][24][25][26][27][28][29][30][31][32] and even recently as anti-COVID agents [33]. The mechanisms of action underlying the antibacterial and anticancer properties of fac-[Re I (CO) 3 ] + species are numerous and not yet fully elucidated.…”
Section: Introductionmentioning
confidence: 99%